Experimental characterization of the bond between externally bonded reinforcement (EBR) CFRP strips and concrete at elevated temperatures. (July 2015) - Firmo, J.P.; Correia, J.R.; Pitta, D.; Tiago, C.; Arruda, M.R.T.
Abstract: This paper presents an experimental study about the bond between concrete and CFRP strengthening systems at elevated temperatures. The experimental campaign consisted of double-lap shear tests on concrete blocks strengthened with CFRP strips externally bonded with epoxy adhesive, conducted in both steady state (series S1) and transient (series S2) conditions. In series S1, two types of specimens were tested, with or without mechanical anchorage on the extremities of the CFRP strips. Specimens were first heated up to temperatures of 20 °C, 55 °C, 90 °C and 120 °C, and then loaded up to failure. In series S2, specimens were first loaded up to 25%, 50% or 75% of their ambient temperature strength and then heated up to failure. The obtained results in specimens without mechanical anchorage show that with increased temperature (i) the strain distributions along the bonded length change significantly, becoming closer to linear due to the epoxy adhesive softening; (ii) the effective bond length increases; (iii) the stiffness and the maximum shear stress of the bond–slip relationships suffer considerable reductions; (iv) the failure mode changes from cohesive (at ambient temperature) to adhesive (at elevated temperature); and (v) the overall stiffness and strength of CFRP–concrete interface decrease significantly, with the bond strength reduction in the transient tests being similar to that observed on the steady-state conditions. The incorporation of the mechanical anchorage, for all temperatures tested (i) led to more uniform axial strain distributions; (ii) presented bond–slip relationships with lower maximum shear stresses; and (iii) provided significantly higher bond strength.